Relación entre el quehacer docente y el perfil de egreso basado en competencias de la carrera Pedagogía Básica de la Universidad de Magallanes (Educational Perspectives Magazine (REPED), 2022)
The following investigation was bom for the worry to know the academics’ thought who formed the teacher group their Works and the way that they haveassumed the new cumculo based in the competentes of the pedagogy in primary education career of Magullan University (made oficial by jeans of the 020/SU/2001 decree). It’s investigated about the level of knoledge that teachers have about the profile of graduation their conceptions about a formation based in competences, the foundations what support their teacher work, the educative intentions and how they relate all these curricular elements with what was declared in the graduation profile.To develop this investigation it was used a intentioned sample, not probabilistic, composed for eight representative academics from the totality of the formation field incluided in the study plan of career.It’s used a methodology of quality investigation, applying interviews in depth to each participant of the research, whore registers give the basic information, when they are codified classified and triangulized, let’ the realization of an análisis and interpretation procers, discovering fundamentaly the following:• A low level of knowledge about the graduation profile of the career.• A combined education conception, in a slow transition procers to word a real understanding of an education based in competences being a sing ofresistance to the curricular change.• A teacher work develops under the new curriculum, but not recognize explicitly for the teachers.The antecedents that confirm this inform of the research, as well as its conclusions give to the academic team of the career a serie of discoverier that will be useful to understand the dinamic that the process has had in the educational innovation process begun eight years ago, as well as, specific clue information to guide the induction, capacitation and development of the teacher.